Kinerja Pegawai Dalam Pengadaan Barang Dan Jasa Secara Elektronik Melalui Aplikasi LPSE UPPBJ Universitas Tadulako - Hafid, Abdul; Juemi; Mini; Ariani, Naora (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The purpose of this research is to determine employee performance in the electronic procurement of goods and services through the LPSE application of UPPBJ Tadulako University and to determine the level of effectiveness of electronic procurement of goods and services through the LPSE application of UPPBJ Tadulako University. The basis of this research is a survey with a descriptive qualitative research type. The location of this research is the Unit Pengelola Pengadaan Barang dan Jasa (UPPBJ). This research uses an informant technique with purposive sampling by determining informants as many as 5 people, consisting of the Chairman, Secretary, and 3 Staff of Tadulako University. Data collection techniques use 3 methods, namely observation, interviews, and documentation. The data analysis technique uses a descriptive qualitative approach, based on employee performance indicators consisting of aspects of productivity, service quality, responsiveness, responsibility, and accountability. The research results show that in terms of productivity, service quality, responsiveness, responsibility, and accountability, they are basically running well but not maximally because they still face obstacles and barriers. Hindering factors include the lack of active participation from regions that still have difficulty accessing the internet, untimely announcements that make people feel cheated, irregularities or lack of control in the LPSE process that allow manipulation to occur, providers from other regions still feeling inequality of access to LPSE, especially for areas that do not have adequate technology infrastructure, information that is still incomplete and unclear, so it must be directed through the interface in the procurement process via the application, and files that are not compatible with the provider's devices.